A review on egomotion by means of differential epipolar geometry applied to the movement of a mobile robot - Armangué, Xavier (2003)
The estimation of camera egomotion is an old problem in computer vision. Since the 1980s, many approaches based on both the discrete and the differential epipolar constraint have been proposed. The discrete case is used mainly in self-calibrated stereoscopic systems, whereas the differential case deals with a single moving camera. This article surveys several methods for 3D motion estimation unifying the mathematics convention which are then adapted to the common case of a mobile robot moving on a plane. Experimental results are given on synthetic data covering more than 0.5 million estimations. These surveyed algorithms have been programmed and are available on the Internet.